Validity and reliability of a field hockey-specific dribbling speed test - Tapsell, L. C.; Binnie, M. J.; Lay, B. S.; Dawson, B. T.; Goods, P. S. (The Journal of Strength and Conditioning Research, 2022)
The present study aimed to design a valid and reliable test for field hockey players that concurrently assesses the skill of dribbling and sport-specific agility. In total, 27 male and 32 female subjects were recruited from amateur (n = 20), state-level (n = 22), and national-level (n = 17) field hockey teams. The test course was developed in consultation with state- and national-level field hockey coaches, and using match analyses from existing literature. Subjects were familiarized before completing a testing session that consisted of 3 maximal-effort trials through a field hockey-specific course while dribbling a hockey ball, and another 3 trials of the same course without dribbling the ball. Amateur and state subjects completed an additional session for test-retest reliability analysis. Electronic timing gates recorded time to complete the course with the ball (DRIBBLE), without the ball (SPRINT), and the difference between DRIBBLE and SPRINT (DELTA). With significance set at p < 0.05, subjects of higher playing levels recorded significantly faster DRIBBLE (p < 0.001) and significantly lower DELTA (p < 0.001) times. No significant difference was found between player levels for SPRINT (p = 0.484) times. Intraclass correlations were 0.84 and 0.81 for DELTA and DRIBBLE, respectively. In conclusion, the dribbling test trialed here has sufficient validity and reliability for use in performance testing of field hockey athletes and can be implemented across playing levels to objectively track skill progression.